Processes and Logics of closed urbanizations in metropolitan areas: Bogotá, Colombia and Buenos Aires, Argentina - Mendoza Jaramillo, Alejandro (Corporación Universitaria del Caribe, CECAR., 2016)
Abstract: The present article makes a brief tour of the logics and processes around one of the phenomena of land occupation most widespread in the Latin American cities –Closed Urbanizations (UC)–, landed in the metropolitan areas of Bogota and Buenos Aires. In this sense, we seek to uncover the peculiarities and similarities in the installation of this real estate product and its possible impact on the configuration of two metropolis, read through three dimensions (population growth, UC installation and urban configuration). ___Keywords: Closed urbanizations, metropolitan areas, Latin American city. ___Resumen: El presente artículo hace un breve recorrido por las lógicas y procesos en torno a uno de los fenómenos de ocupación del suelo más difundidos en las ciudades latinoamericanas –Urbanizaciones Cerradas (UC) –, aterrizado en las áreas metropolitanas de Bogotá y Buenos Aires. En este sentido, se busca develar las particularidades y similitudes en la instalación de ese producto inmobiliario y su posible incidencia en la configuración de dos metrópolis, leído a través de tres dimensiones (crecimiento poblacional, instalación de UC y configuración urbana). ___Palabras clave: Urbanizaciones cerradas, áreas metropolitanas, ciudad latinoamericana. ___Recibido: 31 de Julio de 2016. Aceptado: 5 Septiembre de 2016.